Ca1-xSrxSnO3 (x = 0; 0,25; 0,50; 0,75 e 1): filmes obtidos por métodos físicos e químicos e pós obtidos pelo método dos precursores poliméricos - Alves, Mary Cristina Ferreira (2011)
SrSnO3 and CaSnO3 present orthorhombic perovskite structure, due the distortions and inclination among octahedra. The distortions favor the obtainment of materials with dielectric and semiconductive properties, leading to many applications in the technological area. In this work SrSnO3 powders were obtained by the polymeric precursor method and thin films based on Ca1-xSrxSnO3were obtained by the PLD (pulsed laser deposition) and CSD (chemical solution deposition) methods. Epitaxial films with high crystalline quality were obtained on SrTiO3 (100) substrates while textured and polycrystalline films were obtained on sapphire and silica. The PLD physical method led to films with higher epitaxy degree comparing to CSD, but with a higher short range disorder. An important point was the possibility of variation of short and long range order of powders and thin films as well as of film morphology, from variation of synthesis conditions as temperature, substrate and composition.